Pendampingan Peningkatan Nilai Ekonomi Kacang Buncis Menjadi Produk Olahan di Sembalun Timba Gading - Muhammad Haikal Akram Arya; Wisnu Mahendra; Nur Yatin; Citra Yuniarti; Indradi Rahmatullah; Johan Miranda; Anisa Risti; Putri Imbin Sari; Feni Fatriani; Tika Puspa Sari; Muhammad Sarjan (Unram Journal of Community Service, 2023)
Sembalun Timba Gading Village is one of 6 villages in the Sembalun sub-district. The strategic location of the area makes Sembahun Timba Gading Village very suitable for developing agricultural, plantation and tourism potential. Almost all the people in Sembalun Timba Gading Village work as farmers, but there are some people who work as civil servants, tour operators, MSME movers, etc. However, most of the community's income comes from the agricultural sector. One of the leading commodities of Timba Gading Village is Beans, which are planted and harvested every year. Therefore, Beans is our main focus, in this case Desapreneur, to improve the quality of MSMEs through the development and marketing of processed Beans products